Податкова правосуб'єктність організації - платника податку - Оніщик, Ю.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
The work addresses the features of tax legal personality of organization. It describes the nature and the importance of tax legal personality as well as analyzes its components.